2015
DOI: 10.1371/journal.pone.0111771
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression Profile of Chicken Embryo Fibroblast DF-1 Cells Infected with Cell-Adapted Infectious Bursal Disease Virus

Abstract: RNA-Seq was used to unveil the transcriptional profile of DF-1 cells at the early stage of caIBDV infection. Total RNAs were extracted from virus-infected cells at 0, 6 and 12 hpi. RNA-Seq datasets of respective samples mapped to 56.5–57.6% of isoforms in the reference genome Galgal4.73. At 6 hpi, 23 isoforms underwent an elevated expression, while 128 isoforms were up-regulated and 5 were down-regulated at 12 hpi in the virus-infected group. Besides, 10 isoforms were exclusively expressed in the virus-infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 81 publications
6
25
0
Order By: Relevance
“…This is consistent with a study by Hui et al, which characterized the gene expression of DF-1 cells infected with the D78 strain [35]. Twenty-two of the genes that we identified as being differentially expressed in D78-infected chicken primary B cells were similarly differentially expressed following D78 infection of DF-1 cells.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is consistent with a study by Hui et al, which characterized the gene expression of DF-1 cells infected with the D78 strain [35]. Twenty-two of the genes that we identified as being differentially expressed in D78-infected chicken primary B cells were similarly differentially expressed following D78 infection of DF-1 cells.…”
Section: Discussionsupporting
confidence: 92%
“…Twenty-two of the genes that we identified as being differentially expressed in D78-infected chicken primary B cells were similarly differentially expressed following D78 infection of DF-1 cells. Notably, Hui et al identified that D78 triggered an IFIT5-IRF1/3-Viperin pathway in infected DF-1 cells [35]. In our study, D78 infection also led to the significant up-regulation of IFIT5, IRF1, IRF7 and RSAD2 (Viperin), suggesting that this pathway is also triggered in chicken primary B cells infected with D78.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Moreover, the recognition of IBDV is important for cells to activate their surface markers. Raymond [28] found that chicken DF-1 cells may enhance levels of IFIH1, DHX58, and TRIM25, which possess properties for detecting viral dsRNA.…”
Section: Discussionmentioning
confidence: 99%